Tinjauan Yuridis Putusan Hakim Yang Memutuskan Perkara Tindak Pidana Narkotika Diluar Surat Dakwaan Berdasarkan Pasal 182 Ayat (4) Kitab Undang-Undang Hukum Acara Pidana (Studi Kasus Perkara Nomor: 56/Pid.Sus/2016/PN.Bkt) - Devas, Afifah Fatharani; ', Erdianto; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Daily law enforcement always administration preoccupied by a variety of criminal acts that occurred in the middle of the community, including the crime of narcotics. The crime of narcotics must be dealt with and processed by the criminal justice system. In the process of the trial, the judge who was instrumental in deciding a matter. Under article 182 subsection (4) the book of the law of criminal procedure that the Tribunal Judges do the deliberations to take a decision should be based upon indictment and everything that is proven in the examination at the hearing. In the decision-making there is a possibility the judge memutusakan the matter outside of the indictment. While the indictment was instrumental as the basis of the implementation of the resolution of the criminal case.The purpose of this thesis research namely: first, to find out the consideration of judge decided a matter outside the indictment in the criminal offence of narcotics. Second, to know the legal consequences for the verdict outside the indictment in deciding a matter the crime of narcotics.This type of research is classified in types of juridical normative research, because in this study the authors use the study material libraries such as official documents, books for research. In this study, the source data used the primary data, secondary data and data tertier. Data collecting techniques, in this study with the method of the study of librarianship or documentary studies.From the results of research, there are two things which can be inferred. First, the basic consideration of the Tribunal is judge on the verdict the number 56/Pid. Sus/2016/PN. Bkt Bukittinggi, based on the District Court to the Supreme Court RI circular letter number 07 Year 2012, that the judge can make a legal breakthrough because the judge is not a funnel the Act. Second, the legal consequences for the verdict outside the indictment in deciding a matter the crime narcotics namely annulled by law. Because the ruling is not in accordance with the provisions of the book of the law of criminal procedure as provided for in article 182 subsection (4) the book of the law of criminal procedure. The author's suggestion, first in conducting deliberations for a decision of the Tribunal shall Judge according to the provisions in force. Second, in the Tribunal's ruling the judge had dropped the freedom and interpretation, but still there are restrictions that must be observed. We recommend that the Tribunal judges do not do errors-errors in dropping the verdict against the defendant, the Tribunal shall Judge understand the rules that apply.Keywords: Crime – Indictment – Verdict - Judge